An Exploration of Factors Triggering Employee Shirking through Systematic Reviews and Meta-Analyses - Ukpere, Wilfred; Mitonga-Monga, Jeremy; Mapira, Nyasha (Journal of Economic Development, Environment and People, 2025)
This study sought to systematically review existing literature, whilst developing an understanding of factors that trigger employee shirking. In addition, the study aimed to propose intervention strategies that organizations can use to reduce employee shirking. The study used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines for systematic literature review to gather and analyse related literature. A total of twelve research articles, published between 2020 and 2025, were included in this systematic literature review. The study found several factors that trigger employee shirking such as poor employee monitoring, perceived injustice, poor incentive systems, breach of psychological contract, conflict of interest, undervaluing employee competencies, and misjudging task difficulty. To mitigate employee shirking, employers should monitor their employees closely, set clear roles and expectations, conduct regular performance reviews, and design good incentive systems, which motivate workers to work and provide a safe work environment. This systematic literature review contributes to the existing body of knowledge in human resource management by proposing strategies that organizations and human resource specialists can consider when designing and implementing appropriate mechanisms to curb employee shirking.